2004
DOI: 10.1038/sj.eye.6701503
|View full text |Cite
|
Sign up to set email alerts
|

Cone- and rod-mediated multifocal electroretinogram in early age-related maculopathy

Abstract: Purpose To investigate the cone-and rodmediated multifocal electroretinograms (mfERG) in early age-related maculopathy (early ARM). Methods and subjects We investigated the cone-and rod-mediated mfERG in 17 eyes of 17 subjects with early ARM and 16 eyes of 16 age-matched control subjects with normal fundi. All subjects had a visual acuity of 6/12 or better. We divided the ARM subjects into two groups based on drusen size and retinal pigment epithelium abnormalitiesFa less advanced (ARM1) and a more advanced (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 36 publications
4
54
0
1
Order By: Relevance
“…The authors suggested that delayed implicit times rather than amplitudes reflected chronic retinal ischaemia. 85 A postreceptoral involvement of rod pathways as found in studies with the mfERG in early ARM [38][39][40] is supported by Hood et al 86 who compared the rodmediated mfERG with the full-field rod ERG. They suggested that the rod-mediated mfERG responses are like the full-field rod ERG with mainly bipolar cell responses and a very small photoreceptor contribution.…”
Section: Eyesupporting
confidence: 58%
See 1 more Smart Citation
“…The authors suggested that delayed implicit times rather than amplitudes reflected chronic retinal ischaemia. 85 A postreceptoral involvement of rod pathways as found in studies with the mfERG in early ARM [38][39][40] is supported by Hood et al 86 who compared the rodmediated mfERG with the full-field rod ERG. They suggested that the rod-mediated mfERG responses are like the full-field rod ERG with mainly bipolar cell responses and a very small photoreceptor contribution.…”
Section: Eyesupporting
confidence: 58%
“…32,33 The functional results of these tests cannot be given in detail but all show an impairment of cone-or rod-mediated function (or both) in early ARM. In addition, there is preferential vulnerability of the S-cone 34,35 and rod pathway [36][37][38][39][40][41][42] in early ARM over the L-and M-cone pathway. Curcio 43 has demonstrated that parafoveal rods were the first to die in early ARM and the last surviving photoreceptor in late ARM was a cone.…”
Section: Psychophysical and Electrophysiological Function Tests In Armmentioning
confidence: 99%
“…By contrast, the negligible difference between normal and cfh Ϫ/Ϫ mice under photopic conditions suggests that there is minimal impairment of cone function despite occasional histological changes in the short-wavelength cone population (see below). This is in keeping with the loss of rods and rod function in AMD (19)(20)(21)(22) and in particular impaired scotopic function in the macula (23).…”
Section: Cfh Deficiency Results In Rod Photoreceptormentioning
confidence: 63%
“…By using a special protocol for recording rod-mediated mfERG instead of the conventional cone-mediated mfERG, Feigl et al also showed that rod-mediated mfERG may be more sensitive in detecting retinal dysfunction in early AMD compared with light-adapted conemediated mfERG. 55,56 These results suggest the rod system might be affected earlier than the lightadapted cone system in early AMD. Feigl et al further demonstrated that the use of a global-flash mfERG stimulus by inserting a global bright flash between two dark frames may also detect deficits in early AMD before the conventional mfERG stimulus.…”
Section: Clinical Applications Of Mferg In Acquired Retinal Diseases mentioning
confidence: 79%
“…4,156 As described previously, apart from using mfERG for recording responses from the cone system, rod-mediated mfERG can also be recorded through dark-adaptation and insertion of dark frames between the multifocal flashes in order to study the topographical function of the rod system. 37,38,55,56,92,93,102 Besides using the conventional m-sequence technique in the recording of mfERG, the use of an LCD stimulator has enabled another recording technique called the cyclic-summation method. 168 This method was found to have better signal-to-noise ratio and can provide faster recording time compared to the conventional m-sequence.…”
Section: Developments Of New Recording Parametersmentioning
confidence: 99%